Level of anxiety and results of psychomotor tests in young soccer players of different performance levels - Dominika M. Wilczyńska; Frank Abrahamsen; Agnieszka Popławska; Piotr Aschenbrenner; Marcin Dornowski (Termedia Publishing House, 2021)
The aim of the current study is to determine how the level of state and trait anxiety differs between youth athletes of different performance levels and furthermore whether there are correlations between performance levels and psychomotor variables in the selected tasks. A sample of 97 boys, aged 11-12 years, practising soccer represented two groups: A - high performance level and B - lower performance level. Participants completed a  state and trait anxiety inventory and performed selected psychomotor tests. The analyses demonstrated that the higher the levels of anxiety were, the shorter was the response time and more accurate were the responses in selected psychomotor tests. For the whole group, r = -0.224, p < 0.05, and for group B, r = -0.333, p < 0.05. Moreover, the findings showed a moderator effect of level (group A vs B) on reaction time, which was almost significant in state anxiety and significant in trait anxiety. For group B, trait anxiety was negatively related to reaction time (b = -0.002, SE = 0.001, t = -2.93, p = .004, 95% CI [-0.004, -0.001]). This means that the higher the trait anxiety was, the shorter was the reaction time in group B, but there was no significant effect in group A. The results of the study confirmed the negative correlation between the trait and state anxiety and reaction time. The higher the anxiety was, the shorter was the response time of child soccer players. Future research should determine whether athletes' performance levels do affect performance under stress and replicate the study with different samples such as girls and different sport disciplines.